Penguatan Peran Guru Sebagai Agen Profil Pelajar Pancasila dalam Menanamkan Tanggung Jawab Belajar pada Siswa Sekolah Dasar - Dinda Yarshal; Nila Lestari; Dewi Ftria; Dina Hidyati Hts (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2026)
The Merdeka Curriculum positions teachers as key agents of change in fostering the Pancasila Student Profile, particularly the independent dimension that emphasizes students’ learning responsibility. However, strengthening teachers’ capacity to implement this value in primary schools remains a significant challenge. This Community Service Program aimed to enhance teachers’ competence in integrating learning responsibility into classroom practices. The program was conducted at UPT SD Negeri 064990 Medan Johor and involved 20 teachers through a series of socialization sessions, mentoring, classroom implementation, and evaluation. Program effectiveness was measured using pretest and posttest instruments analyzed with the N-Gain method. The results showed that the average teacher competency score increased from 64.45 to 81.73, with an N-Gain score of 0.49, indicating a moderate level of improvement. Furthermore, 85% of participants achieved good or very good performance on the posttest, with the highest improvement observed in the indicator of teachers serving as role models for character development. These findings demonstrate that a systematic mentoring approach effectively strengthens teachers’ competence in fostering students’ learning responsibility and supports the implementation of the Pancasila Student Profile in primary education.